Design and Economic Growth: Panel Cointegration and Causality Analysis - Bidirici, Melike; Bohur, Eda (ELSEVIER SCIENCE BV, 2015)
Orthodox economic theory does not investigate the connection between design and economic growth in details but design affects the economy. Design is very important for realizing the radical invention for economic growth and it has important roles in industry lifecycle and at different stages of business cycle. In this paper, it was investigated the relationship between sales from production, exports, gross value added (US, Ihr, BKD) and about was investigated from 1982 to 2012 for 1.000 largest firms in Turkey. The data was withdrawn from 1.000 largest firms represented by the Istanbul Chamber of Industry (ICI) in order to determine impacts of design on firms, The firms that undertake design activities and that continuously take place among the top 1000 between 1982 and 2012 and which comply with similar performance criteria and the sector differences for group 4 were neglected. The panel cointegration test and Granger Causality methods were employed to examine the relationship. Granger causality result determined there is evidence of bidirectional causality between the variables (sales from production - labor, sales from production - gross value added and labor) in all groups.
Keywords: Design; Economic Growth; Productivity; Panel Unit Root; Panel Cointegration Test; Business & Economics; Social Sciences - Other Topics